Cardiopulmonary Arrest and Pulmonary Hypertension in an Infant with Pertussis Case Report. (10th March 2021) - Fueta, Patrick Ovie; Eyituoyo, Harry Onoriode; Igbinoba, Oghogho; Roberts, Jon
Abstract : Pertussis is a vaccine-preventable disease with an incidence that has been trending upwards in the United States over the last two decades. This is evident by an increase in the incidence from 10, 100 cases in 1974 to a peak of >48, 000 cases noted in the last decade. Pertussis disease severity ranges from mild to severe, with resultant complications capable of causing significant morbidity and mortality. We report a case of pertussis in a 5-week-old female infant who presented with fever, paroxysms of cough, apnea, and seizures leading to cardiopulmonary arrest. Cardiopulmonary resuscitation lasted 11 minutes before the return of spontaneous circulation. She was transferred to our tertiary facility and admitted to the pediatric intensive care unit. Complete blood count revealed significant leukocytosis, chest X-ray revealed bilateral pulmonary edema with pleural effusion, and echocardiogram demonstrated pulmonary hypertension. Bordetella pertussis infection was confirmed on respiratory polymerase chain reaction. She was treated with antibiotics, ventilatory management, and other supportive care. She was discharged on room air after a hospital course of 7 weeks with care coordination between her primary care provider, pulmonologist, and neurologist. Despite the positive outcome in this case, it is important to note that managing severe pertussis involves multidisciplinary care, and the morbidity and cost implications can be mitigated on a population scale through vaccine optimization strategies.